KONSEP ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI DALAM PERSPEKTIF BARAT DAN ISLAM - Sumiran; Anisul Fuad; Hartadi; M. Sofiandi; Riyad Amrullah (Al Amin : Jurnal Kajian Ilmu dan Budaya Islam, 2025)
This study aims to conduct a comparative analysis of the three fundamental pillars of the philosophy of science—ontology, epistemology, and axiology—from the perspectives of Western and Islamic civilizations. Amidst the dominance of the modern scientific paradigm, which tends toward secularism, this study seeks to explore alternative ways of thinking that integrate the spiritual dimension with rationality. The method used is qualitative, with a descriptive-analytical library research approach to primary and secondary literature. The research findings indicate that, at the ontological level, the West tends to adhere to materialism, which limits reality to the physical dimension, while Islam recognizes a hierarchy of existence between the material realm and metaphysics based on Tawhid (the Unity of God). Epistemologically, the West relies on reason and empiricism as the sole authority, while Islam integrates the senses, reason, and revelation as comprehensive sources of knowledge. From the axiological dimension, Western science, which is value-free, risks triggering a moral and ecological crisis, while Islam offers a value-bound science based on the concepts of Adab (Adab) and the welfare of mankind. This study concludes that integrating Western methodological sophistication with the depth of Islamic spirituality is a strategic step towards building a more holistic and civilized scientific paradigm in the future.